Systematic responses of match high-intensity performance to weekly external training load during a play-off mesocycle - Papadakis, L.; Angelis, A.; Patras, K. (Sport Performance & Science Reports, 2021)
Monitoring training/match load is crucial in identifying patterns and individual responses in adaptation to a training program, risk of non-functional overreaching, injury and illness and readiness to train/compete (1). Whilst previous research examined the effects of training load on match player rank- or skill-related performance (2-4), there is scarce evidence regarding its effects on match running performance (4). Aim: We modeled how the within-player effect of different training load variables on match running performance varies systematically across levels of the between-player effect during a competitive mesocycle. Design: A longitudinal observational study design was selected to examine the cross-level interaction of the within-player effect by the between-player effect.